UPAYA KINERJA SATRESKRIM UPAYA KINERJA SATREKSRIM POLRES TEGAL DALAM PENANGANAN TINDAK PIDANA CURAT GUNA MENINGKATKAN CRIME CLEARANCE DALAM RANGKA POLRI YANG PRESISI: UPAYA KINERJA SATREKSRIM POLRES TEGAL DALAM PENANGANAN TINDAK PIDANA CURAT GUNA MENINGKATKAN CRIME CLEARANCE DALAM RANGKA POLRI YANG PRESISI - Marco Melandri (Advances in Police Science Research Journal, 2022)
ABSTRACT EFFORTS TO IMPROVE THE PERFORMANCE OF SATRESKRIM TEGAL POLICE IN HANDLING CURAT CRIMINAL ACTS TO INCREASE CRIME CLEARANCE IN THE FRAMEWORK OF PRECISION POLICE Marco Melandri, 18.053, marcomelandri10@gmail.com Performance is one of the references of a person's results in carrying out tasks in an organization. This reference can see whether the work done according to the criteria or not. The Reskrim Unit as a repressive function has handled crime cases, especially in the crime of theft by ballast. But the reality is that the settlement of theft cases with ballast has decreased. Therefore, this study wants to explore how efforts in improving the performance of satreksrim Tegal Police in handling curated criminal acts to increase crime clearance in the framework of Precision Police. This research uses a qualitative approach with the type of field study research with the research location at Tegal Police Station. This research also uses the analysis knife of organizational management theory and organizational resources and uses concepts related to the focus of the problem formulated. Based on the results of the study, it can be concluded that efforts to improve the performance of the Tegal Police Station in handling curated criminal acts to increase crime clearance in the framework of precision police, have not been maximally caused by internal factors, namely human resources, infrastructure, budget, and operational standards procedures and external factors that include the community and geographical location of Tegal Regency. For this reason, it is necessary to problem solving of improving the performance of satreskrim Tegal Police in handling curated criminal acts. Keywords: Performance, Curated Crime, Satreskrim Tegal Police